Urban Operating Systems: Diagramming the City. - Marvin, Simon; Luque‐Ayala, Andrés (International Journal of Urban & Regional Research, 2017)
A set of software/hardware packages developed by IT companies for the urban market is transforming the way in which cities are imagined and configured. These urban operating systems (Urban OS) embody important presumptions about what constitutes appropriate knowledge and forms of decision making, pointing to how novel forms of 'smart' or 'computational' urbanism may govern urban life. Arguing that an analysis of the interface between the urban and IT requires a broader historical and theoretical perspective, the article traces the ways in which the city has been diagrammed as a space of power since the nineteenth century and highlights the antecedents of Urban OS present across different domains of life-particularly in military and corporate enterprises. Relaying the urban as an efficient logistical enterprise, and operating as a piloting device (Deleuze and Guattari, 1987), the Urban OS appears as an emerging urban diagram introducing an informational diagrammatic of control. We focus on five archetypal framings of how Urban OS envision the city, illustrating how a new corporate rationality of control based on functional simplification and heterogeneous reintegration seeks to take hold in the city (via re-engineering, agility, modularity, flexibility and configurability).